Culture sensitive design : a guide to culture in practice - van Boeijen, Annemiek, ....-; Zijlstra, Yvo, ....- (Amsterdam : BIS publishers, 2020)
Societies worldwide are increasingly interconnected through trade, migration, education, and digitization. This has resulted in a profound new complexity of cultural groups. Consequently, designers are confronted with the challenge of gaining a clear understanding of this cultural diversity. Culture is a complex phenomenon defined by an ongoing process of shifts in human interactions and experiences. In addition to the functional, technical, and economic requirements, it is primarily culture that defines how any designed object and service will perform and prove itself: a process that largely takes place outside the domain and control of the designer. Culture Sensitive Design provides an overview of theory as well as practical models and methods, aimed to motivate and inspire design students, practitioners, and educators to get in touch with different cultural values, customs, and symbols. It is in order to avoid mistakes that may be obstructive for certain groups of people; to enable cross-cultural cooperation; to learn more about the diverse and complex layers of culture that define who we are, how we think, how we imagine, and how we create; and to open up the design space, thereby creating a tremendous source of new ideas. Richly illustrated with examples of real life situations, the book provides everything necessary to generate optimal circumstances for the best design solutions to emerge.
Keywords: Culture design; Design